Study on Stress Distribution Law of High-Efficiency Paste Backfilling Working Face with Solid Waste in Thick Coal Seam - Meng Zhang; Dan Fang (Advances in Materials Science and Engineering, 2020)
The high-efficiency paste backfilling mining technology of solid waste in thick coal seam above 6 m is a complex system engineering, which involves mining, backfilling, supporting, subsidence, safety, and other aspects, so it is of great strategic significance to study the technology. In this paper, on the basis of comprehensive research methods such as laboratory experiments, theoretical analysis, computer programming, and other comprehensive research methods, aiming at the problems of low production capacity and high paste backfilling cost, taking the mining of No. 3 Coal Seam under buildings in Lu’an area as the research object, the stress distribution law of high-efficiency paste backfilling working face with solid waste in more than 6-meter-thick coal seam was carried out. The main achievements are as follows: On the basis of the theoretical establishment of the program method for the instability discriminant analysis of roof rock beam failure with the change of backfilling body unit strength with time, a numerical calculation model considering the change process of backfilling body strength is established. The stress distribution analysis of the E1302 working face before and during the mining process plays a guiding role in the actual production of the whole working face and roadway. The research results support the sustainable development of coal mining enterprises from technology, which has great economic, social, and environmental benefits, and can promote the industrialization of green mining high-tech in Shanxi Province and even the whole country and can promote the green mining technology progress of paste backfilling in coal mines in China, which is of great significance to the sustainable development of mining production and environmental construction.